A rare case of bilateral acute otitis media leading to bilateral facial paresis in an adult - Singh, Inderdeep; Ranjit, Lakshmi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Facial nerve paresis is a known complication of middle ear disease. However it is more commonly seen as a complication of chronic otitis media as compared to acute otitis media (AOM). There are very few reported cases of AOM leading to facial palsy and even fewer ones of bilateral acute otitis media leading to bilateral facial palsy. Since this is a very rare presentation its management and treatment are not very well outlined as per standard guidelines. Here we have presented a very rare case of bilateral AOM leading to bilateral facial paresis, how the case progressed and how it was managed. We have tried to bring forth the salient features of the presentation, the progression and the resolution of the disease due to the successful management.